1997
DOI: 10.1046/j.1365-2249.1997.4361452.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular cytokine expression in whole blood preparations from normals and patients with atopic dermatitis

Abstract: SUMMARYIn recent years, the importance of characterizing the role of cytokines in a wide range of clinical conditions has resulted in development of new methods to assess cytokine expression in clinical samples. The use of anti-cytokine MoAbs and flow cytometry to detect cytokines intracellularly at the single-cell level has the potential to quantify cytokine production in different diseases. For this technique to be useful in a clinical setting, rapid throughput of clinical samples and a cheap, reliable assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 28 publications
2
25
0
4
Order By: Relevance
“…A contribution by several other cytokines, responsible for a proinflammatory response, such as IL-6 and TNF-␣, or responsible for an anti-inflammatory response, such as IL-10, has been suspected (11,12,21). Most studies have been performed on peripheral blood mononuclear cells (PBMC) and macrophages; only a few have been performed on whole blood (6,7). Using the FMBA we investigated the concentration of cytokines in whole blood of atopic and nonatopic asthmatics and in atopic and nonatopic controls.…”
mentioning
confidence: 99%
“…A contribution by several other cytokines, responsible for a proinflammatory response, such as IL-6 and TNF-␣, or responsible for an anti-inflammatory response, such as IL-10, has been suspected (11,12,21). Most studies have been performed on peripheral blood mononuclear cells (PBMC) and macrophages; only a few have been performed on whole blood (6,7). Using the FMBA we investigated the concentration of cytokines in whole blood of atopic and nonatopic asthmatics and in atopic and nonatopic controls.…”
mentioning
confidence: 99%
“…Whether this can influence subsequent clinical course of AD remains to be elucidated. Although we used flow cytometry to detect intracellular cytokine expression at the single-cell level, as with most authors of the above-cited reports, some differences in technique, including time stimulation, permeabilization, stimulation agents, Golgi apparatus blockers, antibody, and analyzed T cell subsets, could have an impact on our results [10].The small number of subjects may also be a drawback of this study; nevertheless, some differences among the particular subgroups were observed. In our study, we failed to demonstrate a role of IL-4 in patients with AD, but we showed significantly increased total IgE levels and numbers of circulating eosinophils in AD patients compared with the control group.…”
Section: Discussionmentioning
confidence: 96%
“…Rheology is used to measure the viscoelastic properties of fibrin networks using different rheological techniques (Ferry et al 1997;Jansen et al 2013;Kurniawan et al 2016;Piechocka et al 2016). Ferry et al (1997) were the first to study the linear viscoelastic behavior of fibrin clots using torsional rheometry (Ferry et al 1997).…”
Section: Introductionmentioning
confidence: 99%